A comment on "The people think what I think" by Furnas and LaPira (2024) - Grant Baldwin; Clayton Becker; Emily Ortiz; Josh Goetz (Institute for Replication (I4R), 2024)
Furnas & LaPira (2024) examine the extent to which unelected political elites in the United States misperceive nationwide public opinion on salient policy issues. They find that unelected elites consistently misperceive public opinion in the direction of their own opinions on average. They estimate that unelected elites that strongly oppose (support) a policy perceive public opinion in favor of that policy to be about ten percentage points below (above) the actual level of public support. These results persist when considering the ideological underpinnings of each issue, elite partisanship, the relevance of partisanship in profession, elite professional community, and elite trust in partisan information sources. We attempt to reproduce these findings through three methods. First, we run the data analysis code as it was provided by the authors and successfully reproduced the paper's main findings. Second, we test the robustness of the results by generating estimates of public opinion from a separate nationally representative survey administered at the same time as the authors' survey. Lastly, we run additional robustness tests by examining whether results hold under different model specifications. We find that the authors' results are largely robust to these additional analyses.
Keywords: 330